SEMANTIC FEATURES AND DIFFERENCES OF ENTREPRENEURSHIP LEXICON IN ENGLISH AND UZBEK (International journal of artificial intelligence, 2025)
The lexical units related to entrepreneurship in English and Uzbek have unique similarities and differences due to various historical, economic, and cultural factors. While English has a well-developed system of business terminology, Uzbek has adopted numerous foreign terms while maintaining its national lexical structure. Under the influence of globalization, the Uzbek entrepreneurial lexicon continues to expand and evolve with new concepts. This article discusses the semantic features and differences of entrepreneurship-related lexicon in English and Uzbek.